Comparison of peripheral blood T, B, and NK lymphocytes between frontline medical workers for treating patients of COVID-19 and normal outpatient and emergency medical workers in China - He, Weijian; Ma, Piyong; Li, Xiuying; Wang, Yali; Zhang, Yucheng (Frontiers in Psychiatry, 2023)
The outbreak of the novel coronavirus disease 2019 (COVID-19) has led to significant mental stress for frontline medical workers treating patients with confirmed COVID-19 in China. Psychological stress has an impact on the immune system. The number and percentage of lymphocyte subsets are standard indicators of cellular immune detection. Here, we reported the differences in CD3, CD4, CD8, CD19, and CD56 lymphocytes between 158 frontline medical workers and 24 controls from medical staffs of the outpatient and emergency departments. We found that frontline medical workers had significantly lower absolute values and percentages of CD19+ B cells, especially in the female and the aged ≥40 years subgroup. Stratification analysis showed that the absolute values of CD4+ T cells were significantly lower in the aged <40 years subgroup, while percentages of CD8+ T cells were lower and percentages of CD56+ NK cells were higher in the aged ≥40 years subgroup. In summary, this study suggests paying more attention to frontline medical workers’ mental health and immune function, and properly providing them with psychological interventions and measures of care.